Effect of Bacillus subtilis on the growth and survival rate of shrimp (Litopenaeus vannamei) - Zokaeifar, Hadi; Saad, Che Roos; Mohd Daud, Hassan; Harnim, Sharr Azni; Shakibazadeh, Shahram (Academic Journals, 2009)
The effect of Bacillus subtilis, isolated from digestive tract of Macrobrachium rosenbergii was investigated on growth and survival rate of Litopenaeus vannameiduring 60 days of culture. Sixteen aquaria with four replicates were used for treatments and controls. Treatment groups were consisted of і) shrimp fed diet withB. subtilis (T1), and ii) shrimp fed diet mixed with B. subtilis and commercial probiotic (T2). Control groups were consisted of і) shrimp fed diet with commercial probiotic as positive control, and ii) shrimp fed unaltered diet as negative control. Results showed that B. subtilis was proliferated in digestive tract of treated shrimps, and the number of Vibrio spp. was reduced in digestive tract during the cultural period. Survival rate, 75.5± 4.62 %, and yields of shrimps, 190.00 ± 13.13 g, treated with B. subtilis were significantly greater (P<0.05) than the other treated and control groups. Also population density of total viable bacteria and B. subtiliscounted in digestive tract of shrimps treated with B. subtilis were significantly higher (P<0.05) than the other treated groups. Results of this study indicate that the addition of B. subtilis can improve shrimp (L. vannamei) survival rate and yield.